The mirror in medieval and early modern culture specular reflections - Frelick, Nancy M. (Cursor Mundi, 2016)
This volume examines the intersections between material and metaphorical mirrors in medieval and early modern culture. Mirrors have always fascinated humankind. They collapse ordinary distinctions, making visible what is normally invisible, and promising access to hidden realities. Yet, these liminal objects also point to the limitations of human perception, knowledge, and wisdom. In this interdisciplinary volume, specialists in medieval and early modern science, cultural and political history, as well as art history, philosophy, and literature come together to explore the intersections between material and metaphysical mirrors in Europe and the Islamic world. During the time periods studied here, various technologies were transforming the looking glass as an optical device, scientific instrument, and aesthetic object, making it clearer and more readily available, though it remained a rare and precious commodity. While technical innovations spawned new discoveries and ways of seeing, belief systems were slower to change, as expressed in the natural sciences, mystical writings, literature, and visual culture. Mirror metaphors based on analogies established in the ancient world still retained significant power and authority, perhaps especially when related to Aristotelian science, the medieval speculum tradition, religious iconography, secular imagery, Renaissance Neoplatonism, or spectacular Baroque engineering, artistry, and self-fashioning. Mirror effects created through myths, metaphors, rhetorical strategies, or other devices could invite self-contemplation and evoke abstract or paradoxical concepts. Whether faithful or deforming, specular reflections often turn out to be ambivalent and contradictory: sometimes sources of illusion, sometimes reflections of divine truth, mirrors compel us to question the very nature of representation.